Improving the Students Ability in Reading Coprehension through Narrative Text by Using Reciprocal Teaching at the Eight Grade of SMP Negeri 5 Gunungsitoli in 2022/2023 - Reslin Laoli; Kristof Martin Efori Telaumbanua; Trisman Harefa; Hasrat Sozanolo Harefa (Universitas Muhammadiyah Enrekang, 2023)
Reading comprehension is one of the important skills that must be learned by students. However, students had several problems in learning reading comprehension of narrative texts which caused the MCC not to be achieved by students. These problems are lack of vocabulary, unable to find students' main ideas, and unable to identify the generic structure of narrative text. Therefore, the purpose of this research is to improve students' reading comprehension skills in narrative texts through Reciprocal Teaching. This research was conducted in two cycles. Each cycle consists of several procedures, namely planning, action, observation, and reflection. The research instrument used observation sheets, evaluation sheets and field notes. The results of Cycle I showed that most of the students had not been able to reach the MCC. The average grade of students is 50.66. There were 20 students who failed and 10 students who passed the MCC. There were 8 students (26.66%) in fail level, 12 students (40.10%) in less level, 4 students (13.34%) in enough level, 3 students (10%) in Good. and 3 students (10%) in very good category. While in Cycle II, it shows that all students have achieved MCC. The average grade of students is 92.33. There were no students who were put into the less, fail, and enough categories. There were 8 students (26.66%) in good level, and 22 students (73.33%) in very good level. Based on the results above, it can be seen that Reciprocal Teaching has improve students' reading comprehension skills in narrative texts.